Conceptualizing the Influence of Souvenir Image and Place Identity on Souvenir Repurchasing Intentions - Chen, Dong; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
The local traditions, including arts and crafts, are considered as the important things by which the  tourism industry can be attracted by a particular country. The souvenirs are the best tool to tell  friends or family about your concern towards them during traveling. Chinese ceramics are  considered classic souvenirs to purchase while traveling because the ceramic products have been  utilized by the residents for many years. Chinese people have a very significant and firm  attachment to their native products they call them souvenirs. The purchase of souvenirs is an  integral part of a country’s tourism sector. Therefore, this conceptual paper explores the role of  souvenir image, and place identity in boosting the re-purchase intentions of Chinese tourism  industry employees for souvenir products. The researcher has reviewed the existing literature to  propose a framework to investigate the determinants of the re-purchase intentions for souvenir  products. Thus, the study contributed to the existing body of literature on the determinants of re purchase intentions. The proposed research framework has made a significant addition to the  literature.
Keywords: Authenticity value; perceived value; souvenir; repurchase intention; place identity